2013
DOI: 10.1007/s00464-013-3098-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of probe-based confocal endomicroscopy with virtual chromoendoscopy and white-light endoscopy for diagnosis of gastric intestinal metaplasia

Abstract: pCLE was superior to AFI and WLE for diagnosing GIM. Off-site review improved performance of pCLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 12 publications
1
32
0
1
Order By: Relevance
“…Because the use of CLE becomes more widespread due to the expanding role of CLE in the diagnosis of gastric 17,18 and pancreatic lesions, 19 it may feature more prominently in the diagnostic and management algorithm for IBD in the future. 20 Our study demonstrated that endomicroscopy has enabled for the first time the identification of local barrier dysfunction in the duodenum of patients with CD and UC.…”
Section: Discussionmentioning
confidence: 99%
“…Because the use of CLE becomes more widespread due to the expanding role of CLE in the diagnosis of gastric 17,18 and pancreatic lesions, 19 it may feature more prominently in the diagnostic and management algorithm for IBD in the future. 20 Our study demonstrated that endomicroscopy has enabled for the first time the identification of local barrier dysfunction in the duodenum of patients with CD and UC.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1143 studies were identified after primary literature search, among them 1133 were excluded due to their manuscript types, irrelevant to the topic, duplicates, or with no data on diagnostic efficacy of CLE. Finally, 10 studies fulfilled the inclusion criteria and were eligible in this study . The study selection process is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Information of per-lesion but not per-patient analyses was provided by all included studies. The CLE and white-light endoscopy were used to diagnose IM in all of included studies plus virtual chromoendoscopy was also performed in one study [24]. Additionally, virtual chromoendoscopy magnifying flexible spectral imaging color enhancement (ME-FICE) and p-CLE were applied to detect GIM in another study [20].…”
Section: Resultsmentioning
confidence: 99%